Influences of acids on morphology and properties of TiO2 grown on electrospun PVDF fibers. (October 2019) - Zhang, Zhi-Guang; Liu, Hui; Wang, Xiao-Xiong; Zhang, Jun; Zhang, Fu-Bao; Li, Ru; Yu, Miao; Ramakrishna, Seeram; Long, Yun-Ze
Abstract: TiO2 with different crystalline phases and morphologies was grown on poly(vinylidene fluoride) (PVDF) fibers through electrospinning followed by hydrothermal synthesis in different acidic environments. The structural and morphological characteristics of the as-prepared composites were studied. The results show that the type and the concentration of the acids have a decisive influence on the crystalline phase, morphology, and loading mass of the TiO2 grown on the PVDF fiber. The formation of anatase TiO2 is favored in the hydrothermal environment of H2 SO4 and CH3 COOH, whereas rutile TiO2 is more readily obtained in HCl and HNO3 . The morphology and the mass of the grown TiO2 undergo a significant change with increasing acid concentration. Four samples were selected from the TiO2 /PVDF composites hydrothermally synthesized in H2 SO4, HNO3, HCl, or CH3 COOH to perform photocatalytic degradation of rhodamine B under 40 W UV lamp irradiation for 120 min. The TiO2 /PVDF sample hydrothermally synthesized in H2 SO4 showed the highest photodegradation efficiency (about 63.2%) owing to its excellent optical performance, the highest TiO2 loading mass, and the lowest photogenerated electron-hole recombination rate. Graphical abstract: Image 1 Highlights: TiO2 /poly(vinylidene fluoride) (PVDF) fibers were hydrothermally synthesized in three strong acids and a weak acid. The crystalline phases, morphology, and yield of the loaded TiO2 were studied. The growth mechanism of TiO2 /PVDF fibers was studied. The photocatalytic performance of TiO2 /PVDF fibers was investigated.